Exploring Help-Seeking Predictors Among Colombian Victims of Intimate Partner Violence in Different Age Groups. (February 2023) - Padilla-Medina, Diana M.; Small, Eusebius; Pavlova Nikolova, Silviya
This study examined the extent, source, and individual, microsystem, exosystem, and macrosystem-level (Heise's Ecological Model) predictors of help-seeking behaviors among women of different age groups in Colombia. Data on 12, 915 married or cohabitating women who had experienced diverse forms of intimate partner violence (IPV) were obtained from the Colombia Demographic Health Survey 2015. More than half of the Colombian women who reported some form of IPV experience did not seek any help. Women aged 25–39 were less likely to seek help. Type of violence and experience of IPV and education were the strongest predictors of help-seeking among women in all age groups. Implications for research and programming are discussed.